THE NOYION OF ADMINISTRATIVE AND LEGAL STATUS OF PERSONS OF THE CREW OF AN AIRCRAFT OF UKRAINE - Дараганова, Н. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
In the article the author reveals the concept and content of the administrative and legal status of the crew of the aircraft of Ukraine.